Primary Open-Angle African American Glaucoma Genetics (POAAGG) Study: gender and risk of POAG in African Americans - Khachatryan, Naira (PLoS One, 2019)
The purpose of this study was to investigate the association between gender and primary open-angle glaucoma (POAG) among African Americans and to assess demographic, systemic, and behavioral factors that may contribute to differences between genders. The Primary Open-Angle African American Glaucoma Genetics (POAAGG) study had a case-control design and included African Americans 35 years and older, recruited from the greater Philadelphia, Pennsylvania. Diagnosis of POAG was based on evidence of both glaucomatous optic nerve damage and characteristic visual field loss. Demographic and behavioral information, history of systemic diseases and anthropometric measurements were obtained at study enrollment. Gender differences in risk of POAG were examined using multivariate logistic regression. A total of 2,290 POAG cases and 2,538 controls were included in the study. The percentage of men among cases was higher than among controls (38.6% vs 30.3%, P<0.001). The subjects’ mean age at enrollment was significantly higher for cases compared to controls (70.2±11.3 vs. 61.6±11.8 years, P<0.003). Cases had lower rates of diabetes (40% vs. 46%, P<0.001), higher rates of systemic hypertension (80% vs. 72%, P<0.001), and lower body mass index (BMI) (29.7±6.7 vs. 31.9±7.4, P<0.001) than controls. In the final multivariable model, male gender was significantly associated with POAG risk (OR, 1.64; 95% CI, 1.44–1.87; P<0.001), after adjusting for age, systemic hypertension, diabetes, and BMI. Within the POAAGG study, men were at higher risk of having POAG than women. Pending genetic results from this study will be used to better understand the underlying genetic variations that may account for these differences.